2017
DOI: 10.18203/2320-6012.ijrms20170145
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of package inserts of orally administered drugs available in the Indian market

Abstract: Background:The package insert of a medication forms an important source of information to the patient while taking a drug. The package insert is expected to contain complete information regarding the drug aiding the patient to obtain additional knowledge regarding the drug. Methods: 100 package inserts of orally administered drugs were obtained from local chemists and were analysed according to the Sections 6.2 and 6.3 of Schedule D (II), Drugs and Cosmetics Act (1940) and Rules (1945). Results: The posology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…Antibacterial class was also found maximum in studies conducted by Deepak et al, Sudhamadhuri et al and Shruti et al 17,1,19 Oral as route of 1,17,[19][20][21] As per the guidelines evaluated according to Drugs and Cosmetic Act 1945 (Table 1) undesirable effects were mentioned in 98% of the evaluated package inserts which is more as compared to studies conducted by Deepak et all where it was mentioned only in 37.69% and Chhaya et al where it was mentioned in 97% of the evaluated package inserts. 17,22 In the present study pregnancy and lactation was mentioned in 98% of the evaluated package inserts which is more in comparison to study conducted by Deepak et al where it was mentioned in 37.69% and Chhaya et al where it was mentioned in 89% and Sudha et al where it was mentioned in 84%. 17,20,22 As per the guidelines mentioning of Method of administration and precautions of use as found out in present study was 80% and 90% which was similar to the study conducted by Sudhamadhuri et al 1 In present study antidote was mentioned in 40% of the evaluated package 100 package inserts which was more compared to studies conducted by Sudhamadhuri et al where only 20% is mentioned, 13% in a study conducted by Chhaya et al and Kalam et al where it is mentioned in only 4%.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Antibacterial class was also found maximum in studies conducted by Deepak et al, Sudhamadhuri et al and Shruti et al 17,1,19 Oral as route of 1,17,[19][20][21] As per the guidelines evaluated according to Drugs and Cosmetic Act 1945 (Table 1) undesirable effects were mentioned in 98% of the evaluated package inserts which is more as compared to studies conducted by Deepak et all where it was mentioned only in 37.69% and Chhaya et al where it was mentioned in 97% of the evaluated package inserts. 17,22 In the present study pregnancy and lactation was mentioned in 98% of the evaluated package inserts which is more in comparison to study conducted by Deepak et al where it was mentioned in 37.69% and Chhaya et al where it was mentioned in 89% and Sudha et al where it was mentioned in 84%. 17,20,22 As per the guidelines mentioning of Method of administration and precautions of use as found out in present study was 80% and 90% which was similar to the study conducted by Sudhamadhuri et al 1 In present study antidote was mentioned in 40% of the evaluated package 100 package inserts which was more compared to studies conducted by Sudhamadhuri et al where only 20% is mentioned, 13% in a study conducted by Chhaya et al and Kalam et al where it is mentioned in only 4%.…”
Section: Discussionsupporting
confidence: 40%
“…17,22 In the present study pregnancy and lactation was mentioned in 98% of the evaluated package inserts which is more in comparison to study conducted by Deepak et al where it was mentioned in 37.69% and Chhaya et al where it was mentioned in 89% and Sudha et al where it was mentioned in 84%. 17,20,22 As per the guidelines mentioning of Method of administration and precautions of use as found out in present study was 80% and 90% which was similar to the study conducted by Sudhamadhuri et al 1 In present study antidote was mentioned in 40% of the evaluated package 100 package inserts which was more compared to studies conducted by Sudhamadhuri et al where only 20% is mentioned, 13% in a study conducted by Chhaya et al and Kalam et al where it is mentioned in only 4%. 1,21,22 In the present study contraindication was present in 96% of the evaluated package inserts which was similar to a study conducted by Chhaya et al however more than the result as obtained by Shruti et al and Sowmya et al which was 91%.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…At the same time, for the physicians also package inserts serve as an important source of drug information prescribing effectively and safely as many a times, it is not possible for the doctors to go through the research articles and look for recent advances in relation to a particular drug. 3 Since, a good Package Insert (PI) is evidence-based and is updated time to time as relevant preclinical and clinical data becomes available, therefore, it can prove to be of immense importance to physicians also. 4 In India, the concept of package insert is governed by the 'Drugs and Cosmetics Act (1940) and Rules (1945)'.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, Shivkar[ 10 ] and Kalam et al .,[ 11 ] in separate studies, reported that most PIs did contain information on therapeutic indications, contraindications, undesirable effects, etc., but there were also important gaps in clinically important information. In a more recently published study on PIs of oral drugs,[ 12 ] the author reported broadly similar findings and concluded that there is wide variation in the information available in PIs circulating in the Indian market.…”
Section: Discussionmentioning
confidence: 67%